Sports Nutrition - Current Recommendations - Ziegenhagen R; Braun H; Carlsohn A; Großhauser M; Heseker H; König D; Mosler S; Nieß A; Oberritter H; Schäbethal K; Schek A; Stehle P; et al. (Deutsche Zeitschrift für Sportmedizin)
This position paper deals with safety aspects of the use of dietary supplements (DS) in sports. DS are legally classified as foodstuffs and may contain vitamins, minerals and other substances with a nutritional or physiological effect. In the case of other substances with a nutritional or physiological effect, it is currently not specifically regulated, with a few exceptions, which individual substances may be added, provided the products are still classified as foods. DS are offered in a wide variety and can be purchased worldwide via the internet. In Germany, they are only subject to a notification requirement before being launched on the market; they are not subject to safety assessment by state authorities. The manufacturers/distributors of the DS are responsible for their safety and for ensuring that consumers are not misled by the product presentation and promotion.For athletes, a balanced diet that is adapted to their needs is a basic requirement and one of the preconditions for good athletic performance. DS are no replacement for a balanced diet.In sports, the use of DS or products that contain micronutrients and other substances with a nutritional or physiological effect should not be conducted uncritically. Possible risks, such as an unintentional violation of anti-doping regulations or potential health risks, should be considered. Key Words: Doping Risk, Wada Prohibited List, Health Risks, Vitamins, Minerals, Caffeine